Damage assessment in adult IgA vasculitis. Cross-sectional results of a multicentre cohort - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2020)
Objective. Immunoglobulin (Ig) A vas-culitis affects children more commonly than adults and previous literature lacks any formal damage assessment. Our aim in this study is to investigate the disease course, relapse rates and prog-nostic factors in adult patients with IgA vasculitis and to evaluate the disease-related damage. Methods. We assembled a retrospective cohort of adult IgA vasculitis from six tertiary Rheumatology Centres in Turkey. The demographics, clinical characteris-tics, treatment and outcomes of patients were abstracted from medical records. Results. The study included 130 (male/female: 85/45) patients and the mean age was 42.2 +/- 17 years. Cutaneous manifestations and arthritis/arthralgia were the most common clinical mani-festations. One hundred thirteen pa-tients (86.9%) were treated with oral glucocorticoids (GC). As additional immunosuppressive (IS) agents, aza-thioprine was given to 44 (34.9%) and pulse cyclophosphamide to 18 (12.6%) patients. Seventy-nine patients (60%) had follow-up of median 15 (IQR 7-40) months. Twelve (15%) patients re-lapsed during follow-up. The mean VDI score was 0.4 in the last visit. Nineteen (24.7%) patients had at least one dam-age item at the end of follow-up. Most frequent damage items were renal 11 (42%), ocular 4 (15%) and cardiovas-cular 4 (15%). Conclusion. In this cohort the most fre-quent damage item was renal and was related to the disease itself. Damage score was higher in patients with more severe disease and treated more aggres-sively. Our results suggest that more ef-fective treatment options are needed in a subgroup of patients with IgA vasculitis to prevent the damage related with the vasculitis, especially with more severe disease.
Keywords: immunoglobulin A vasculitis; Henoch Schonlein purpura; damage; prognosis; leukocytoclastic vasculitis; HENOCH-SCHONLEIN PURPURA; PREDICTIVE FACTORS; CLINICAL SPECTRUM; GENE POLYMORPHISM; RENAL INVOLVEMENT; CHILDREN; NEPHRITIS; DISEASE; MANIFESTATIONS; PROGNOSIS